2011
DOI: 10.1007/s00442-011-2158-y
|View full text |Cite
|
Sign up to set email alerts
|

Incidental nest predation in freshwater turtles: inter- and intraspecific differences in vulnerability are explained by relative crypsis

Abstract: There has long been interest in the influence of predators on prey populations, although most predator-prey studies have focused on prey species that are targets of directed predator searching. Conversely, few have addressed depredation that occurs after incidental encounters with predators. We tested two predictions stemming from the hypothesis that nest predation on two sympatric freshwater turtle species whose nests are differentially prone to opportunistic detection-painted turtles (Chrysemys picta) and sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 58 publications
(91 reference statements)
0
18
0
Order By: Relevance
“…We cannot discount the possibility that removal, processing, and reburial of eggs by researchers in the first 24 h affected depredation rates, especially at the start of incubation. although we present data for the first 72 h post-oviposition, we are aware they may not be indicative of depredation rates on nests from which eggs were not removed (Congdon et al 1983;Tinkle et al 1981;Christens and Bider 1987;Burke et al 2005;strickland et al 2010;geller 2012;Wirsing et al 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We cannot discount the possibility that removal, processing, and reburial of eggs by researchers in the first 24 h affected depredation rates, especially at the start of incubation. although we present data for the first 72 h post-oviposition, we are aware they may not be indicative of depredation rates on nests from which eggs were not removed (Congdon et al 1983;Tinkle et al 1981;Christens and Bider 1987;Burke et al 2005;strickland et al 2010;geller 2012;Wirsing et al 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Many studies of turtle nest depredation report that most depredation events occur within the first week post-oviposition (Tinkle et al 1981;Christens and Bider 1987;Congdon et al 1983Congdon et al , 1987Robinson and Bider 1988;Burke et al 2005;strickland et al 2010;geller 2012;Wirsing et al 2012;Holcomb and Carr 2013). For example, Congdon et al (1983) found that 87% of Blanding's Turtle (Emydoidea blandingii) nest depredation occurred within the first 5 days post-oviposition.…”
Section: Introductionmentioning
confidence: 99%
“…However, predation may continue throughout incubation and may even show a peak near the approximate time of hatching, indicating either that cues persist throughout incubation or that predators can use chemosensory, auditory, or other cues associated with hatching to find late-term nests (Snow 1982;Wirsing et al 2012;Mitchell et al 2014;Riley and Litzgus 2014).…”
Section: Introductionmentioning
confidence: 97%
“…High nest predation can substantially limit recruitment in some species and in extreme cases can lead to population declines. Nest predation is often higher in anthropogenically impacted environments because populations of "subsidized" predators, such as raccoons (Procyon lotor (L., 1758)) that scavenge from waste bins in urban or recreational areas, are not limited by the natural carrying capacity of the area (Boarman 1997;Wirsing et al 2012). Where predator populations become particularly large they can have substantial impacts, particularly on declining, threatened populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation